Influence of uterine manipulator use on the incidence of lymphovascular propagation in the treatment of endometrial cancer. Issue 1 (1st February 2023) - Hudec, Boris; Dókuš, Karol; Urdzík, Peter; Školka, Richard; Koňarčíková, Tatiana; Smitka, Michal
Abstract: Background: Endometrial cancers are among the epithelial malignancies of the lining of the uterine cavity. The invasion of carcinoma into the lymphovascular space (LVSI) is considered a risk factor for the course of the disease. Material and methods: We evaluated 170 female patients. Our primary objective was to find any difference in the incidence of LVSI in female patients treated with and without an intrauterine manipulator. In addition, we analyzed the effect of the type of intrauterine manipulator used on the incidence of LVSI, tumor grading, myometrial invasion, and the method of obtaining primary histology with regard to the incidence of LVSI. Results: Using a manipulator during surgery was not associated with LVSI (with a manipulator vs. without, 11.5 vs. 21.7%; OR 1.8; 95% CI 0.73–4.39; p  = 0.199). However, the method used to obtain the primary histology had a statistically significant effect on the incidence of LVSI in our set ( p -value = 0.011). Conclusions: In our study, we did not confirm the effect of a uterine manipulator on the possible increase of LVSI positive cases. The secondary analysis indicated a higher incidence of LVSI in the female patients diagnosed with curettage than in those who underwent hysteroscopy. Trail registration: Trail is registered in ClicincalTrails.gov with identifier: NCT05261165.